Arc-enhanced glow discharge ion etching of WC-Co cemented carbide for improved PVD thin film adhesion and asymmetric cutting edge preparation of micro milling tools - Lopes Dias, Nelson Filipe; Meijer, Alexander Leonard; Jäckel, Christoph Paul; Frisch, Alexander; Biermann, Dirk; Tillmann, Wolfgang (Technische Universität Dortmund, 2024)
Wear-resistant thin films on cutting tools require effective ion etching to enhance adhesion and thus extended tool service life. Arc enhanced glow discharge (AEGD) ion etching, characterized by high ionization degrees and high etch rates, was applied to ultrafine-grained WC-Co cemented carbide, commonly used for micromilling cutters. The effect of AEGD ion etching on the surface integrity of WC-Co and the resulting adhesion behavior of a TiAlSiN thin film was investigated by varying the etching time in comparison with conventional glow discharge (GD) ion etching. In addition, the impact of intensive etching on the cutting edge geometry of micro end cutters and, in turn, on the cutting performance in micromilling of hardened and annealed high-speed steel was evaluated. AEGD achieves remarkable etch rates of 12 nm/min at extended etching times, which are 100 times greater than conventional glow discharge (GD) ion etching. Prolonged AEGD ion etching for ≥30 min removes entire near-surface WC grains and exposes carbides beneath, resulting in increased surface roughness. After the etching process, polished WC-Co substrates exhibit a slight reduction in residual compressive stresses, which steadily decrease with increasing AEGD ion etching time. Furthermore, a TiAlSiN thin film demonstrates high adhesion on AEGD-etched surfaces compared to GD ion etching. Even a brief 5 min AEGD ion etching ensures the highest adhesion class according to the Rockwell C indentation test. Moreover, the intensive material removal results in significant changes in cutting edge geometry of micro end cutters, yielding substantial cutting edge rounding and an asymmetrical shape with form-factors Κ ≥ 2. In cutting tests, the resulting cutting edge geometries effectively reduce the wear formation and the associated wear-related increase in process forces during micromilling hardened and tempered powder metallurgical high-speed steel. In summary, AEGD ion etching emerges as a highly effective method for both enhancing thin film adhesion and preparing adapted asymmetrical cutting edge geometries for micromilling tools.
Surface & coatings technology; 491
Keywords: Ion etching; Pretreatment; Cemented carbide; Magnetron sputtering; TiAlSiN; Micromilling; 620; 670; Ionenstrahlätzen; Vorbehandlung <Technik>; Hartmetall; Hochleistungsimpulsmagnetronsputtern; Titanaluminide; Fräsen